Exploring the Effectiveness of Métis Women’s Research Methodology and Methods: Promising Wellness Research Practices - Gaudet, Janice; Dorion, Leah; Corrigal Flaminio, Anna (First Peoples Child & Family Review, 2020)
In this article, we share our experience conducting research with Métis women as Métis women researchers. We engaged in promising research practices through visiting, ceremony, and creative methods of art and writing embedded in what we identify as a learning-by-doing practice. Through collaborative and Indigenous relational methodology, we sought to support a culturally safe, nurturing space where Métis women could learn from one another and express Métis knowledge about the specific roles and responsibilities of Métis Aunties within our respective kinship system. This inquiry into the roles of Métis Aunties included a creative art and writing dialogue event in the Métis river community of St. Louis in Saskatchewan, attended by women who were Métis Aunties or nieces. The purpose of the event was to learn more about our Métis Aunties, building on Dr. Kim Anderson’s (2016) extensive research on women’s roles in the governance, care, and wellness of our healthy/balanced kinship systems. We chose this specific region because of its historical significance to Métis people as a river place, and our own personal connections to Métis families in this area. We share our processes in learning with and from other Métis women in order to contribute to the growing literature on relational approaches to research.